HAK CERAI PEREMPUAN DALAM HUKUM KELUARGA ISLAM MAROKO - Daud, Fathonah K.; Syarif, Nurrohman (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This paper examines the women’s right to divorce under Moroccan Islamic family law. This article relies on a statutory approach, accompanied by interviews. Most of the data were taken from Moroccan regulations on marriage. The data were also collected from books and journals on women and divorce in Moroccan Law. Additionally, interviews are conducted to enrich information. The result of this study shows that Morocco recognizes the right of woman to divorce (her husband) in two terms: tatliq li al-syiqaq and khulu'. Of these two rights, Moroccan women share an equal position with men in the chance to end marital ties. Following the divorce, Moroccan family law stipulates that joint property belongs to the wife, except for immovable assets in the husband's name. Due to this provision, Moroccan women's bargaining position is arguably strong, because they have the legal ‘power’ to negotiate whether the marriage should be continued or ended. This should encourage husbands to behave carefully of their wives during the marriage. Theoretically, Moroccan family law can be said progressive in terms of protecting the rights of women (and their child/s). Tulisan ini mengkaji hak bercerai bagi perempuan dalam undang-undang keluarga yang diterapkan di negara muslim Maroko. Artikel ini ditulis dengan pendekatan perundang-undangan (statue approach) yang dilengkapi dengan wawancara. Data dikumpulkan dari peraturan-peraturan perkawinan di Maroko. Data juga didapatkan dari buku-buku dan jurnal yang membahas hak perempuan untuk bercerai. Di samping itu, data juga diperkaya melalui wawancara. Hasil penelitian ini menunjukkan bahwa Maroko mengakui hak perempuan untuk menceraikan (suaminya) dengan dua jalan, yaitu: tatliq li al-syiqaq dan khulu’. Dari kedua hak menceraikan ini, perempuan Maroko mempunyai kedudukan yang cukup imbang dengan laki-laki dalam kemampuan memutuskan ikatan perkawinan. Pasca perceraian, hukum keluarga Maroko menetapkan harta bersama jatuh kepada istri, kecuali harta tidak bergerak yang atas nama suami. Dengan ketentuan ini, posisi tawar perempuan Maroko dapat dikatakan cukup kuat karena mereka memiliki modal negosiasi apakah pernikahan dilanjutkan atau tidak. Ini menjadi isyarat bagi para suami untuk berprilaku hati-hati kepada istrinya dalam berumah tangga. Secara teoretis, hukum keluarga Maroko dapat disebut progresif dalam memberikan perlindungan kepada hak-hak perempuan, termasuk hak-hak anak-anak.